Teaching and Learning Genetics with Multiple Representations - Tsui, Chi-Yan (Curtin University, 2003)
This study investigated the secondary school students' learning of genetics when their teachers included an interactive computer program BioLogica in classroom teaching and learning. Genetics is difficult to teach and learn at school because it is conceptually and linguistically complex for students who have little or no prior knowledge about it. Yet genetics is now central to learning and research in biomedical sciences and is essential for understanding contemporary issues such as genetic engineering and cloning. Interactive multimedia programs such as BioLogica have provided new opportunities for learning as these programs feature multiple external representations (MERs) of knowledge in different formats, including visualgraphical and verbal-textual and at different levels of organisation. Users can manipulate and observe the behaviour of these MERs. Ainsworth (1999) summarised three functions of MERs claimed by researchers in supporting learners - to provide complementary information or processes, to constrain interpretations of phenomena and to promote construction of deeper understanding of the domain. Using an interpretive, case-based research approach with multiple methods and multiple sources of data, this study was guided by two foci of inquiry - teachers' integration and implementation of BioLogica in their classroom teaching, and students' learning with BioLogica alongside other resources. The theoretical framework drew on perspectives from educational psychology, the conceptual learning model in science education, and cognitive/computational sciences.Student learning was interpreted using a multidimensional conceptual change framework (Tyson, Venville, Harrison, & Treagust, 1997)-social/affective dimension in terms of students' interests and motivations, epistemological dimension in terms of genetics reasoning of six types (Hickey & Kindfield, 1999), and ontological dimension in terms students' gene conceptions (Venville & Treagust, 1998). Teaching and learning with BioLogica were also analysed and interpreted using Ainsworth's three functions of MERs. Necessary techniques including triangulation were used to increase the rigour of data analysis and interpretation in keeping with the qualitative research tradition. The study was conducted during the years 2001 and 2002 at six classroom sites across four senior high schools of different contexts in the metropolitan Perth area in Western Australia. Five teachers and their Year 10 students (four classes) and Year 12 students (two classes) - 117 students (90 girls and 27 boys), aged from 14 to 18, - participated in the study. Data were collected in response to the initial research questions and the reformulated case-specific research questions. The findings in terms of general assertions were generated from within-case and cross-case analyses and interpretations. Findings of the study suggest that teachers idiosyncratically incorporated (rather than integrated) BioLogica activities in their classroom teaching based on their beliefs and referents for normal classroom teaching. The teachers' implementation and scaffolding of student learning with BioLogica were affected by their knowledge of the software and beliefs about its usefulness based on the salient features of the MERs rather than their functions.Institutional support, technical issues, and time constraints were the possible barriers for using BioLogica in teaching. The findings also suggest that most students were motivated and enjoyed learning with BioLogica but not all who were actively engaged in the activities improved their genetics reasoning. Mindfulness (Salomon & Globerson, 1987) in learning with the BioLogica MERs, learning together with peers, scaffolded learning within the zone of proximal development (Vygotsky, 1978) were deemed important to students' conceptual learning. The postinstructional gene conceptions of most students were not sophisticated and were generally intelligible-plausible (IP) but not intelligible-plausible-fruitful (IPF). While most students identified two salient features of BioLogica MERs, visualisation and instant feedback, some students who substantially improved their reasoning believed that these two features helped their understanding of genetics. Overall, students exhibited social/affective (motivational) and epistemological conceptual change but little or no ontological change. The findings have implications for further and future research. First, Thorley's status analysis is useful in analysing multidimensional conceptual change (Tyson et al., 1997). Second, MERs have provided new learning opportunities and challenges for classroom learning and science teacher education. Third, there is urgency for improving Year 10 genetics teaching and learning. Fourth, the notion of multiple representations is promising in unifying theoretical constructs in psychology, cognitive/computational sciences, science education and science teacher education.